Chicken soup for the mother's soul: 101 stories to open the hearts and rekindle the spirits of mothers - Canfield, Jack (Health Communications, 1997)
Chichen soup for the Mother's Soul pays tribute to motherhood the universal calling that requiere the skils of a master mediador, mentor, cook and couselor.